Membangun Masa Depan: Pentingnya Konseling Karier bagi Remaja - Apriani; Abdul Awal Dzikir (Universitas Palangka Raya, 2026)
This study aims to analyze the importance of career counseling for adolescents in shaping future orientation, particularly in dealing with career confusion, social and family pressures, peer influence, economic considerations, and digital information disruption. This study employed a qualitative approach with an instrumental case study design. Data were collected through in-depth interviews with five informants, consisting of Guidance and Counseling teachers, lecturers or experts in social psychology, and informants with reflective experience in adolescents’ career decision-making. Data were analyzed using the Miles, Huberman, and Saldaña model through the stages of data condensation, data display, and conclusion drawing and verification. The findings revealed three main results. First, career counseling serves as a psychological and pedagogical foundation for helping adolescents recognize their potential, interests, talents, and values, as well as build self-confidence in planning their future. Second, adolescents’ career confusion is influenced by family pressure, peer influence, economic conditions, collectivist culture, and exposure to digital information that often shapes career choices based on trends rather than mature self-exploration. Third, career guidance and counseling services need to shift from administrative and disciplinary services toward more personalized, reflective, digital, humanistic, and future-resilience-oriented services. This study concludes that career counseling is not merely a service that provides information about academic majors or occupations, but an important educational strategy for strengthening adolescents’ self-efficacy in making conscious, adaptive, and sustainable career decisions.